Graphene Oxide-Gold Star Construct on Triangular Electrodes for Alzheimer's Disease Identification - Chang, Wenlong (J Anal Methods Chem, 2021)
Nanotechnology is playing a major role in the field of medical diagnosis, in particular with the biosensor and bioimaging. It improves the performance of the desired system dramatically by displaying higher selectivity and sensitivity. Carbon nanomaterial, gold nanostructure, magnetite nanoparticle, and silica substrate are the most popular nanomaterials greatly contributed to make the affordable and effective biosensor at low-cost. This research work is introducing a new sensing strategy with graphene oxide-constructed triangular electrodes to diagnose Alzheimer's disease (AD). MicroRNA-137 (miRNA-137) was found as a suitable biomarker for AD, and the sensing method was established here to detect miRNA-137 on the complementary sequence. To enhance the immobilization of capture miRNA-137, gold nanostar (GNS) was conjugated with capture miRNA and immobilized on the GO-modified surface through an amine linker. This immobilization process enhanced the hybridization of the target and reaches the detection limit at 10 fM with the sensitivity of 1 fM on the linear curve with a regression coefficient of 0.9038. Further control sequences of miRNA-21 and single and triple base mismatched miRNA-137 did not show a significant response in current changes, indicating the specific miRNA-137 detection for diagnosing AD.